2020
DOI: 10.1109/access.2020.2975118
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Inverse Piezoelectric Effect and Trap Effect in AlGaN/GaN HEMTs Under Reverse-Bias Step Stress at Cryogenic Temperature

Abstract: The inverse piezoelectric effect and trap effect in GaN HEMTs under the high electric field by reverse-bias step stress at cryogenic temperature (CT, 77K) have been investigated. It is found that the inverse piezoelectric effect is suppressed while the trap effect is enhanced at CT. Due to the lower tensile stress in the as-grown AlGaN barrier at CT, the amplitude of the critical voltage related to inverse piezoelectric effect increases from 75V at 300K to 100V at CT, mitigating the irreversible degradation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…The changes in the gate leakage current that occurred after application of different voltage stresses are shown in figure 1(b). A significant increase in the magnitude of the gate current I G was observed when a critical voltage of V Gstress = −60 V was reached, as shown in the inset of figure 1(b), which represents the typical degradation behavior caused by the inverse piezoelectric effect [6,8,9].…”
Section: Gate Leakage Current and Conduction Mechanismmentioning
confidence: 92%
See 1 more Smart Citation
“…The changes in the gate leakage current that occurred after application of different voltage stresses are shown in figure 1(b). A significant increase in the magnitude of the gate current I G was observed when a critical voltage of V Gstress = −60 V was reached, as shown in the inset of figure 1(b), which represents the typical degradation behavior caused by the inverse piezoelectric effect [6,8,9].…”
Section: Gate Leakage Current and Conduction Mechanismmentioning
confidence: 92%
“…The inverse piezoelectric effect was found to be affected by low temperature conditions. Zhu et al reported that the irreversible degradation of the devices was mitigated because of the lower tensile stress related to the inverse piezoelectric effect that occurred at low temperatures [8]. It is therefore desirable to consider the reverse bias stressing degradation, and particularly the variations in the trap characteristics that occur under low temperature conditions when compared with those that occur at room temperature, to provide a systematic study of the inverse piezoelectric effect and enable optimization of the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…• brittle cracking, induced by heavy mechanical stress caused by the mismatch in thermal expansion coefficient (CTE) between SiC and other materials used in semiconductor manufacturing [25], • electron trapping effect of GaN devices [26], and • inverse piezoelectric effect of GaN devices [27], Therefore, the potential difference in the reliability of GaN and SiC technology may appear in the specific operating conditions, closely related to the target application -e.g. repetitive short circuit conditions or repetitive third quadrant operation.…”
Section: A Case Study: Dfr Procedures For Pebb Modulementioning
confidence: 99%
“…10(b). In 2018, Mazumdar et al reported that the inverse piezoelectric effect in GaN HEMTs may also cause the formation of nanocracks, and the formation process can be de-scribed by Griffith's theory of brittle fracture [34] . When an electric stress is applied on a GaN HEMT, the inverse piezoelectric effect occurs and extra mechanical stresses are introduced into the epilayer.…”
Section: High Electric Stressmentioning
confidence: 99%